1997
DOI: 10.1038/sj.onc.1200981
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 induces tyrosine phosphorylation of SHP-2 through IL-2 receptor β chain

Abstract: Coupling of interleukin-2 (IL-2) to the IL-2 receptor (IL-2R) induces rapid increase in tyrosine phosphorylation of cellular substrates through activation of non-receptor protein tyrosine kinases. Here, we report that stimulation through the IL-2R induced tyrosine phosphorylation of the SH2-containing protein-tyrosine phosphatase SHP-2 in F7, a hematopoietic BAF-B03 transfectant clone expressing the IL-2Rb chain. The tyrosine phosphorylation of SHP-2 was speci®c since another protein-tyrosine phosphatase SHP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Further work is required to determine which receptor(s) of IL-24, and phosphatases mediated its effects. In physiological conditions, SHP-1 and SHP-2, are recruited to the IL-2R␤ and dephosphorylate proteins of the JAK/STAT family, thereby terminating the IL-2-induced signal (50,51). We indeed observed that SHP-1 is present in huge amounts in CLL (data not shown).…”
Section: Discussionmentioning
confidence: 54%
“…Further work is required to determine which receptor(s) of IL-24, and phosphatases mediated its effects. In physiological conditions, SHP-1 and SHP-2, are recruited to the IL-2R␤ and dephosphorylate proteins of the JAK/STAT family, thereby terminating the IL-2-induced signal (50,51). We indeed observed that SHP-1 is present in huge amounts in CLL (data not shown).…”
Section: Discussionmentioning
confidence: 54%
“…This cell line has been widely used for studying proliferative responses to a range of cytokines, including IL-2, IL-3, IL-4, erythropoietin, and granulocytemacrophage colony-stimulating factor. [30][31][32][33][34][35][36] Previous studies with BaF-B03 cells have shown that there are at least 3 pathways that may cooperate to produce a proliferative signal. 37 The results of the present study emphasize the pivotal role of the cyclin:CDK-pRB: E2F-1 pathway in mediating the cellular proliferative response in BaF-B03 cells and suggest that multiple pathways converge at E2F-1.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments showed that SHP-2 is involved in the development and differentiation of all lineages of hematopoietic cells, such as erythroid progenitors, myeloid and lymphoid cells [9][10][11]. SHP-2 has also been implicated in the signaling of cytokine receptors that signal via the common c-chain, the shared b-chain and the receptor subunit gp130 such as IL-2, IL-3 or IL-6 [12][13][14][15][16]. However, experiments showing functional consequences of SHP-2 in IL-2 signaling were performed in transfected fibroblasts or in unequally activated T cells, but not in synchronized primary T cells [15,17].…”
Section: Introductionmentioning
confidence: 99%